Subjective Population of Personality: Socio-Psychological Aspects - Zavatskyi, Vadym; Zavatskyi, Yurii; Spicka, Liana (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The paper is aimed at identifying the influence of socio-psychological factors on the formation of subjective wellbeing of a married person. The following methods were used: questionnaire, psycho diagnostic techniques for investigating satisfaction with marriage, personal self-fulfillment in the family (on the operational level and the level of values and role sets), socio-psychological adaptation, conformity of family values and role expectations in marriage. The data about the content, structural components (cognitive and evaluation, value and motivational, emotional and behavioral) and functions (regulatory, prognostic, developmental) of subjective well-being of a married person have been presented. Socio-psychological factors of subjective well-being of a married person have been specified